Stomatal VPD Response: There Is More to the Story Than ABA. Issue 1 (6th October 2017) - Merilo, Ebe; Yarmolinsky, Dmitry; Jalakas, Pirko; Parik, Helen; Tulva, Ingmar; Rasulov, Bakhtier; Kilk, Kalle; Kollist, Hannes
Abstract : ABA level is important for steady-state stomatal conductance, and OST1 is crucial for air humidity-induced stomatal closure. Abstract: Guard cells shrink and close stomatal pores when air humidity decreases (i.e. when the difference between the vapor pressures of leaf and atmosphere [VPD] increases). The role of abscisic acid (ABA) in VPD-induced stomatal closure has been studied using ABA-related mutants that respond to VPD in some studies and not in others. The importance of ABA biosynthesis in guard cells versus vasculature for whole-plant stomatal regulation is unclear as well. Here, we show that Arabidopsis ( Arabidopsis thaliana ) lines carrying mutations in different steps of ABA biosynthesis as well as pea ( Pisum sativum ) wilty and tomato ( Solanum lycopersicum ) flacca ABA-deficient mutants had higher stomatal conductance compared with wild-type plants. To characterize the role of ABA production in different cells, we generated transgenic plants where ABA biosynthesis was rescued in guard cells or phloem companion cells of an ABA-deficient mutant. In both cases, the whole-plant stomatal conductance, stunted growth phenotype, and leaf ABA level were restored to wild-type values, pointing to the redundancy of ABA sources and to the effectiveness of leaf ABA transport. All ABA-deficient lines closed their stomata rapidly and extensively in response to high VPD, whereas plants with mutated protein kinase OST1 showed stunted VPD-induced responses. Another strongly ABA-insensitive mutant, defective in the six ABA PYR/RCAR receptors, responded to changes in VPD in both directions strongly and symmetrically, indicating that its VPD-induced closure could be passive hydraulic. We discuss that both the VPD-induced passive hydraulic stomatal closure and the stomatal VPD regulation of ABA-deficient mutants may be conditional on the initial pretreatment stomatal conductance.